Implementasi Program BKB HI Melalui Sekolah Orang Tua Hebat (SOTH) Guna Mendukung Penurunan Stunting Di Kota Surabaya - Kholifah Saputriani, Yunda; Hartono, Supri (Saraq Opat: Jurnal Administrasi Publik, 2024)
This research is motivated by the achievements that have been achieved in the city of Surabaya regarding the acceleration of stunting reduction through Integrative Holistic Toddler Family Development (BKB HI) with the East Java BBKN innovation program, namely the School for Great Parents (SOTH). SOTH is an effective and targeted stunting prevention method that has been implemented in the city of Surabaya. The results of this research show that the implementation of the SOTH Program has accelerated the rate of reduction in stunting rates in the city of Surabaya with a significant decline starting in 2021-2022. The author in this research used a qualitative-descriptive research approach with data collection techniques through interviews, observation and documentation. This research was conducted by the author to explore, discover and explain the implementation of Integrative Holistic Toddler Family Development through the SOTH program to support the acceleration of stunting reduction. This research shows the results that the Development of Toddler Families through the SOTH program in Sukolilo District has been optimally implemented with evidence of a reduction in the number of stunted toddlers in Sukolilo District, but its achievement needs to be further optimized so that Surabaya at the end of 2023 will be zero stunting, and in 2024 it will be free from stunting cases.